Physical Property Analysis of Biodegradable Film Made from Garut Starch, Glycerol, and Citric Acid - Alit Istiani; Yusmardhany Yusuf; Fauzan Irfandy; Mitha Puspitasari (Eksergi, 2022)
The biodegradable film is an attempt to reduce the use of plastics that cannot be decomposed by nature. This study described biodegradable films produced from arrowroot starch using the casting method. As a plasticizer and crosslinker, glycerol and citric acid are added. The investigation results indicate that the biodegradable film has a clear white color; the greater the amount of starch, the more opaque the color. The tensile strength test results also indicate that the biodegradable film’s tensile strength will be greater the more starch is used, but its percent elongation at break will decrease, or its characteristics will become less elastic. In contrast, adding citric acid demonstrates that the tensile strength decreases due to the hydrolysis of glycosidic linkages in starch.